1998
DOI: 10.1097/00005392-199807000-00087
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterisation of the Dendritic Cell Infiltrate in Prostate Cancer

Abstract: This is the first time that DC have been studied in prostate cancer using the relatively new DC specific monoclonal antibodies CD83 and CMRF-44. These findings suggest that there is no active recruitment of DC into prostate cancer and those DC present are only minimally activated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…This has now been studied in several human cancers. Immunohistological analysis of renal cell carcinoma suggested that DCs were present in normal numbers in the malignant tissue and no evidence of increased activation was found [59]. Similar findings were made in prostate cancer [60], and by us [61] and others [62] in breast cancer.…”
Section: In Human Cancersupporting
confidence: 85%
“…This has now been studied in several human cancers. Immunohistological analysis of renal cell carcinoma suggested that DCs were present in normal numbers in the malignant tissue and no evidence of increased activation was found [59]. Similar findings were made in prostate cancer [60], and by us [61] and others [62] in breast cancer.…”
Section: In Human Cancersupporting
confidence: 85%
“…DCs isolated from mouse and human tumors have been shown to be resistant to a variety of maturation signals in vitro ; however, this block in maturation can be readily reversed by the addition of anti‐IL‐10 antibodies to culture conditions (163, 217, 218). Interestingly, these immature DCs tended to be more tolerogenic than immunogenic APCs with decreased production of IL‐12 and TNF‐α and increased secretion of IL‐10 and TGF‐β (199, 219–222). Recently, the role of DC‐derived IL‐10 in DC‐based tumor immunology was investigated employing DCs derived from IL‐10‐deficient mice.…”
Section: Antagonism Of Il‐10 In Promoting Anti‐tumor Immunitymentioning
confidence: 99%
“…[1][2][3][4] DC activate both naive and memory CD4 ϩ and CD8 ϩ T cells [35][36][37] and seem to meet all requirements as a strong immune-activator for anti-tumor immunity or immunity against microbial infection. [38][39][40] Located in most host tissues, DC function as immune sentinels for infectious agents and inflammatory products of bacteria. Immature DC can capture antigens in peripheral tissues and undergo maturation processes to stimulate naive T cells in secondary lymphoid organs.…”
Section: Pl Is Involved With Erk P38 Kinases and Nf-k Kb P65mentioning
confidence: 99%